Dreyer's English : good advice for good writing (adapted for young readers) - Dreyer, Benjamin (New York Delacorte Press, 2021)
"An informative and witty guide to writing and grammar, written especially for a younger audience"--
The stuff in the front . The life-changing magic of tidying up (your prose) -- Assorted things to do (and not to do) with punctuation -- 2, 3, go: the treatment of numbers -- A little grammar is a dangerous thing -- The realities of fiction -- The stuff in the back. Notes on, amid a list of, frequently and/or easily misspelled words -- Pet peeves -- The confusables -- Notes on proper nouns -- The trimmables -- The miscellany -- Outro: by the way of conclusion -- Things I like.
Includes index.
Ages 10 up
HB
Keywords: English language -- Rhetoric -- Juvenile literature; Exposition (Rhetoric) -- Juvenile literature; English language -- Grammar -- Juvenile literature; English language -- Usage -- Juvenile literature; English language -- Errors of usage -- Juvenile literature